Forensic Investigation of Smartphone Cloud Storage Applications - Aiza Aqeel Abbasi; Shahzad Saleem; Roha Zulqarnain (NUST Journal of Engineering Sciences, 2017)
Advancement in technology allows people to access the data through smartphones regardless of the time and place. Because of widespread applications of users’ interest, the dependency on the mobile devices has increased. Cloud storage applications are attracting user’s attention rapidly and will continue enjoying this ever increasing popularity in the near future as well. This makes them an important potential container of evidence during the investigation. So, it is important for forensic practitioners to match their pace with technological advancements. This paper has addressed the above-mentioned problem as per NIST methodology; bit-by-bit image(s) of android phone is analyzed for exploring the containers for retrieving important artifacts of user activities. The study aims to possibly help the investigative process by scrutinizing cloud storage applications namely: Cubby and IDrive. As a result, interesting locations were identified from where security vulnerabilities and other short comings were exposed. Overall the study concludes that security of Cubby is far better than IDrive.